Site‐directed spin labeling‐electron spin resonance mapping of the residues of cyanobacterial clock protein KaiA that are affected by KaiA–KaiC interaction. (4th February 2014) - Ishii, Kentaro; Terauchi, Shun; Murakami, Reiko; Valencia Swain, Jonathan; Mutoh, Risa; Mino, Hiroyuki; Maki, Kosuke; Arata, Toshiaki; Ishiura, Masahiro
<x xml:space="preserve">Abstract</x> The cyanobacterial clock proteins KaiA, KaiB and KaiC interact with each other to generate circadian oscillations. We have identified the residues of the KaiA homodimer affected through association with hexameric KaiC (KaiC6mer) using a spin‐label‐tagged KaiA C‐terminal domain protein (KaiAc) and performing electron spin resonance (ESR) analysis. Cys substitution and/or the attachment of a spin label to residues located at the bottom area of the KaiAc concave surface, a KaiC‐binding groove, hindered the association of KaiAc with KaiC6mer, suggesting that the groove likely mediates the interaction with KaiC6mer. The residues affected by KaiC6mer association were concentrated in the three areas: the concave surface, a lobe‐like structure (a mobile lobe near the concave surface) and a region adjacent to both the concave surface and the mobile lobe. The distance between the two E254, D255, L258 and R252 residues located on the mobile lobe decreased after KaiC association, suggesting that the two mobile lobes approach each other during the interaction. Analyzing the molecular dynamics of KaiAc showed that these structural changes suggested by ESR analysis were possible. Furthermore, the analyses identified three asymmetries in KaiAc dynamic structures, which gave us a possible explanation of an asymmetric association of KaiAc with KaiC6mer.